SINTESIS KATALITIK 2,2-DIISOPROPOKSIPROPAN DARI ISOPROPANOL UNTUK MENINGKATKAN ANGKA OKTAN BAHAN BAKAR TERBARUKAN - Rianto, Agus; Islamiyah, Islamiyah; Pambudi, Khoir Eko; Al Mufih, Abdul Afif (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2014)
Research has been carried out 2,2-diisopropoksipropan catalytic synthesis of isopropanol to increase the octane number of renewable fuels. Catalytic Synthesis using Cu catalyst that falls on activated carbon (Cu / AC) for use as a process of dehydration of isopropanol to 2.2-diisopropoksipropan. This study also aims to obtain the optimum time and temperature for the dehydration of isopropanol. Preparation of carbon carried by softening coconut shell charcoal to 60-80 mesh size, then heated at a temperature of 800 Â° C, washed, dried, impregnated with CuCl2 and reduced at 400 Â° C with flowing hydrogen gas. The amount of metal content of Fe, Ca, and K in the carbon after the process of washing / soaking determined using Atomic Absorption Spectroscopy (AAS). Activated carbon and catalyst acidity was determined by adsorption of ammonia, isopropanol dehydration process with catalyst Cu / activated carbon (Cu / AC) carried out in an electric furnace with temperature variation: 250; 300; 350; 400; and 450 Â° C and the variation in the amount of catalyst amount: 6; 8; and 10 grams, with Nâ flowed at a rate of 20 mL / min as the carrier gas, and no water vapor. Dehydration results in vapor cooled condenser and then collected for analysis by gas liquid chromatography (GC) and gas chromatography mass spectrometry (GC-MS). The results of the analysis using AAS showed that the presence of washing, soaking using 3 M HCl, the metal Fe, Ca, and K in the activated carbon is significantly reduced. The results of ammonia adsorption analysis showed that activated carbon and Cu / AC has acidity, respectively for 2.962 and 4.911 mmol / g. Catalytic activity of Cu / AC highest achieved at a temperature of 450 Â° C with a catalytic amount of 10 grams of 2,2-diisopropoksipropan produce as much as 61.82%.Keywords: Â Catalytic Dehydration, isopropanol, 2,2-diisopropoksipropan, Cu / activated carbon